Agama, budaya, dan etika sosial - Ayunda, Rina Dwi (Maliki Interdisciplinary Journal, 2023)
Religion is something that must be known about the meaning contained in it, and religion is based on psychological characteristics in the form of belief, so that the strength or fragility of religion depends on how far the belief is embedded in the soul. Religion is a subject of belief that some people think can bring them happiness and benefits in this world and in the hereafter. Conflicts between adherents of religions can sometimes be caused by problems with religion. Meanwhile, the term culture can be interpreted as the totality of behavior patterns, arts, beliefs, institutions, and all other works and human thoughts that characterize the condition of a society or population that are transmitted together. In the Big Indonesian Dictionary (KBBI), culture is defined as: mind; customs; something that has developed; something that becomes a habit that is difficult to change. Social ethics is the regularity of life that is carried out by a person or group related to daily life in the form of association with various examples of the social environment at school, college, community, or family so that social relations here are in accordance with the expected vision and mission. Religion, culture, and social ethics are a unit that provides order in the social life of society to create a society that lives in an orderly manner so as to create a sense of security, comfort, peace without the emergence of fears of religious or social conflicts that could undermine the social order. The existence of religion and culture underlies the creation of a sense of security in society.